Unveiling Life’s Symbols: A Semiotic Analysis of the Lampung Poem Kemumu by Fitri Yani - Arini Mildawati; Heru Prasetyo (Wiyata Budaya: Jurnal Pendidikan Dalam Konteks Humaniora, 2024)
This study analyzes the Lampung poem Kemumu by Fitri Yani using Ferdinand de Saussure's semiotic approach, focusing on the concepts of signifier and signified. The signifier refers to the material form of a sign, such as words or images, while the signified is the concept or meaning associated with the sign. Employing a qualitative method through a literature study, this research explores the symbolism and profound meanings within the elements of Kemumu. The analysis reveals that each line of the poem reflects impermanence, transformation, and the cycle of life through natural symbols such as taro leaves, black stones, and moonlight. This study highlights the relevance of Saussure's theory in understanding the structure and symbolism of poetry, uncovering life's meanings in a complex and profound manner.